The LIQUID SOAP FORMULATION OF AVOCADO (Persea americana) ETHANOL EXTRACT AGAINST Staphylococcus aureus BACTERIA: FORMULASI SABUN CAIR EKSTRAK ETANOL KULIT ALPUKAT (Persea americana) TERHADAP BAKTERI Sthapylococcus aureus - Suryani, Ade Irma (Journal of Pharmacy Tiara Bunda, 2025)
Avocado peels contain Flavanoid compounds and alkaloids as antibacterial. In this study, the ethanol extract of Avocado peels was formulated as a liquid soap using concentrations of FI (1%), FII (3%) and FIII (5%). The aim of this study was to formulate a liquid soap from a sample of Avocado peel extract against the antibacterial activity of Staphylococcus aureus using the agar diffusion method in wells. Physical evaluation of liquid soap preparations includes several parameters, namely organoleptic tests including odor, shape and color, pH test, foam stability test, viscosity test and homogeneity test. The results obtained from testing liquid soap using ethanol extract of Avocado peels with varying concentrations of 1%, 3% and 5% can inhibit the growth of Staphylococcus aureus bacteria, namely 1% = 19.6, 3% = 21.6 and 5% = 25.8. Based on the results of this study it can be concluded that the ethanol extract of Avocado peels (Persea americana) can be formulated in the form of liquid soap and is effective against inhibition of Staphylococcus aureus bacteria. And in this study FIII fulfilled the physical quality evaluation test and had activity as an antibacterial, with the resulting inhibition zone at a concentration of 5% = 26.6 mm, very strong category.